PENGARUH NARKOTIKA TERHADAP TINGKAT KENAKALAN REMAJA DI KELURAHAN PEKAN TANJUNG MORAWA KECAMATAN TANJUNG MORAWA KABUPATEN DELI SERDANG - Ali Akbar, Nelvitia Purba (NERACA KEADILAN, 2025)
This study aims to determine the effect of drug abuse on the level of juvenile delinquency in Pekan Tanjung Morawa Village. The problem of narcotics is a global phenomenon that has a serious impact, especially on the younger generation. This study uses an empirical legal approach and quantitative descriptive methods. Data were obtained through questionnaires and interviews with adolescents, parents, and the Head of the Village and the Pekan Tanjung Morawa Village apparatus. The results of the study indicate that drug abuse has a significant impact on increasing juvenile delinquency such as criminal acts, promiscuity, and decreased achievement. Factors that influence include the social environment, family conflict, educational environment and weak supervision. Preventive and rehabilitation efforts need to be increased to reduce the number of drug abuse among adolescents. The results of this study are to determine how much Impact the Influence of Narcotics has on the Level of Juvenile Delinquency in the Pekan Tanjung Morawa Village area, Deli Serdang Regency.